فقه المصالح والمفاسد عند ابن دقيق العيد من خلال شرحه لحديث البراء: أمرنا رسول الله بسبع: Jurisprudence of Benefits and Evils through Ibn Daqiq Al-Eid’s Explanation of the Hadith of Al-Bara Bin Azib: "The Messenger of Allah commanded us With Seven and forbade us from seven - سعد بوضلعة (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص الشريعة الإسلامية شريعة كاملة، مبناها وأساسها على الحِكَم ومصالح العباد في المعاش والمعاد، ومن هذا المنطلق أتت هذه الدراسة لبحث موضوع من المواضيع التي تشتدّ الحاجة إلىها في كلّ زمان ومكان، وله تعلّق بمقاصد الشريعة، وهو فقه المصالح والمفاسد، وإبراز شيء من جهود إمام من أئمة الإسلام، وإسهاماته فيه، حيث اتفقت كلمة علماء الملة في زمنه وما بعده على الشهادة له بالرسوخ في العلم والاستقامة وخدمة الشريعة خدمة عظيمة، وهو الإمام أبو الفتح تقي الدين محمد ابن دقيق العيد المتوفى سنة: 702 هــ. وتناول هذا الموضوع دارسة فقه المصالح والمفاسد من خلال شرح ابن دقيق العيد في كتابه شرح الإلمام لحديث من جوامع كلم النبي عليه الصلاة والسلام عليه مدار كثير من الأحكام الأصولية والفروعية، وهو شرح موسّع حافل بالفوائد العظيمة من كلّ علم، ومنها علم المقاصد. وقد وضّحت الدراسة بعض الجوانب المهمّة التي لها صلة وثيقة بهذا العلم، وخاصة المصالح والمفاسد والقواعد المتعلّقة بها، وما تفرّع عنها من تطبيقات مهمّة للغاية لابن دقيق العيد، ونكت دقيقة مرتبطة بها. Abstract Islamic Sharia is a complete law, its foundation and principles based on wisdoms and the interests of people in the world and the hereafter. From this point of view, this study came to discuss a topic that is much needed in every time and place, and it has to do with the purposes of Sharia, which is the jurisprudence of Benefits and Evils, and to highlight some of the efforts of one of the prominent Islamic scholars, and his contributions to it, as the scholars of the religion in his time and beyond agreed to testify to him with firmness in knowledge and integrity and contributes to the Sharia a great contribution, and he is Imam Abu Al-Fath Taqi Al-Din Muhammad Ibn Daqiq Al-Eid, died in the year: 702 AH. This topic dealt with the study of the jurisprudence of Benefits and Evils through the explanation of Ibn Daqiq al-Eid in his book, Explanation of Knowledge of a Hadith from the shortest sayings of the Prophet (peace and blessings of Allah be upon him), which of many principles and rulings of Islamic Shari’ah revolves on it. The study clarified some of the important aspects that are closely related to this science, especially the benefits and evils and the rules related to them, and the very important applications that branched from them for Ibn Daqiq al-Eid, and precise benefits associated with them.